BIOCHEMICAL MARKERS IN VITREOUS HUMOR: AN EFFECTIVE METHOD FOR POSTMORTEM INTERVAL ESTIMATION (Journal of Forensic Medicine & Toxicology, 2025)
Background: Estimating the post-mortem interval (PMI) also referred as time since death (TSD) is a challenging task for forensic experts during autopsies. Among various bodily fluids, vitreous humor offers advantages, including ease of access, low contamination risk, and stability. This study aims to determine the time since death using biochemical markers in vitreous humor. Methods: This research was conducted at the Department of Forensic Medicine, Shaheed Hasan Khan Mewati Government Medical College, Nuh, Haryana. A total of 81 medico-legal autopsies with a known time of death were included. Upon collection, vitreous humor samples were immediately centrifuged. Several biochemical markers, including sodium, potassium, and chloride concentrations, were analyzed using appropriate techniques. Results: Significant correlations were found between the concentrations of sodium, potassium, and chloride in vitreous humor, specifically within the first 40 hours post-mortem. These markers demonstrated a reliable pattern for estimating the time since death. Conclusion: The biochemical analysis of vitreous humor, particularly the concentrations of sodium, potassium, and chloride, provides valuable information for estimating the post-mortem interval. This study highlights the potential of vitreous humor as an effective and accessible sample for forensic investigations. Further research with larger sample sizes and diverse conditions is recommended to enhance the accuracy of PMI estimation.
Keywords: Post-mortem interval; Vitreous humor; Biochemical markers; Sodium; Potassium; Chloride